2002
DOI: 10.1073/pnas.192561299
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of estrogen receptor β in terminal differentiation of mammary gland epithelium

Abstract: The mammary glands of prepubertal estrogen receptor (ER)␤؊͞؊ mice are morphologically indistinguishable from those of WT littermates. It appears that, although ER␤ is expressed in the mouse mammary gland, it is not involved in ductal growth of the gland. In this study, we examined the possibility that ER␤ has a role in the differentiated function of the mammary gland. Pregnancy is rare in ER␤؊͞؊ mice, but an intensive breeding program produced seven pregnant ER␤؊͞؊ mice, of which five did not eat their offspri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
154
1
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(166 citation statements)
references
References 34 publications
4
154
1
7
Order By: Relevance
“…There is decreased expression of E-cadherin, connexin 32, occludin, and integrin ␣2 in mammary glands (15) and of ␣-catenin and plectin in the colon (18). These changes are accompanied by alterations in cytoarchitecture as revealed by EM (15,18,19).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is decreased expression of E-cadherin, connexin 32, occludin, and integrin ␣2 in mammary glands (15) and of ␣-catenin and plectin in the colon (18). These changes are accompanied by alterations in cytoarchitecture as revealed by EM (15,18,19).…”
Section: Discussionmentioning
confidence: 96%
“…Although ER␣ is the predominant ER in the adult rodent uterus, ER␤ mRNA has also been detected in WT and ER␣ Ϫ/Ϫ mouse uteri (11). Targeted disruption of ER␤ in mice (12) has revealed roles for ER␤ in differentiation of various epithelial and nonepithelial cell types in many tissues and organs (13)(14)(15)(16)(17)(18)(19). In the uteri of ER␤ Ϫ/Ϫ mice, there is an exaggerated responsiveness to E 2 , resulting in enlargement of the lumen, increase in volume and protein content of uterine secretion, and induction of aberrant epithelial expression of PR after E 2 injection (13).…”
mentioning
confidence: 99%
“…In support of this, abnormal epithelial growth, expression of the proliferation marker Ki67, and age-related cystic breast disease were observed in one model of BERKO mice [57,69]. However, these results have not been replicated in other BERKO mouse models, and normal mammary gland histology was observed in a recently developed model of old BERKO females [41].…”
Section: Potential Role Of Erα/erβ Heterodimers In Biological Responsmentioning
confidence: 97%
“…In BERKO mice, this development is not impaired, nor is lactation [19]. However, one group has observed decreased terminal differentiation, adhesion molecule expression, and increased proliferation marker expression in the alveoli of lactating BERKO mice [57].…”
Section: Erα and Erβ Expression And Activitiesmentioning
confidence: 99%
“…In fact, it has been reported that ERa and ERb have opposite effects on AP1 sites and that they probably have different roles as regards regulation of AP1-dependent genes, including genes involved in the control of cell growth and viability (12). In the mammary gland, ERa and ERb are pivotal for tissue development and terminal differentiation, respectively (13,14). In line with this, 17b-E 2 (hereafter referred to as E 2 ) has been reported to promote the growth of immortalized mammary cells through ERa and inhibit it through ERb (15).…”
mentioning
confidence: 99%